Liquid printing ink composition, and printed matter and laminate using same
Patent Information
- Application Number
- JP2024534746
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-12-15
- Filing Date
- 2023-11-30
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2043-11-30
AI Technical Summary
【0011】 本発明により、低温時に析出が生じることがなく、広範囲な種類のフィルムに適用することができ、優れたラミネート強度を有するリキッドインキ組成物を提供することができる。本発明のリキッドインキ組成物は、押出しラミネートにおいてもドライラミネートにおいても優れたラミネート強度を実現できる。
Smart Images

Figure 0007608674000001 
Figure 0007608674000002 
Figure 0007608674000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a liquid printing ink composition that can be used as a gravure ink or a flexographic ink, and to a printed matter and a laminate using the same. [Background technology]
[0002] Gravure ink and flexographic ink are widely used to impart beauty and functionality to printed materials. When gravure- or flexographically printed materials are used as packaging materials, especially food packaging, they are generally laminated. In this case, various printed materials and lamination processes are used depending on the type of contents and the purpose of use.
[0003] In recent years, packaging materials have become more diverse, and the conditions for adhesion of printing ink to printing substrates and blocking resistance (the phenomenon in which the ink film transfers to the non-printed surface when a film printed with ink is stored in a rolled up state) are becoming stricter every year, including from the perspective of improving work efficiency. Furthermore, from the perspective of both work hygiene during printing and the harmfulness of packaging materials, restrictions on the use of aromatic solvents such as toluene and ketone-based solvents such as methyl ethyl ketone are also required. For example, Patent Document 1 discloses the use of ethylene glycol-containing polyurethane resin as an ink that is excellent in lamination strength and boil / retort properties even when organic solvents that do not contain aromatic organic solvents are used.
[0004] However, among the films used in film packages, there is a tendency for high-performance films with various barrier properties to be increased. These high-performance films have inorganic or organic barrier coating agents applied to their surfaces, and when these high-performance films are used as raw rolls for gravure printing or flexographic printing, the adhesion between the raw roll of film and the ink is often hindered compared to general films. For this reason, printing inks with high lamination strength for various films are desired. In addition, printing inks with high lamination strength are desired in both lamination methods, namely extrusion lamination, which is produced by melt extruding molten polyolefin and laminating it, and dry lamination, which is laminating a plastic film on the printed surface via an adhesive. However, even if the lamination strength is improved, other basic performances such as low-temperature crystallinity may be inferior, so it is not easy to obtain a well-balanced ink by improving the lamination strength while maintaining the low-temperature crystallinity. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6299765 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a liquid ink composition which does not precipitate at low temperatures, can be applied to a wide variety of films, and has excellent lamination strength. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above-mentioned problems, and as a result have found that using a polyester polyol containing two or more diols as reaction raw materials, and essentially containing ethylene glycol as the diol, and a polyurethane resin using a diol having 1 to 20 carbon atoms in a liquid ink composition is effective in solving the problems.
[0008] That is, the present invention is a liquid ink composition containing a binder resin containing a polyurethane resin (A) and an organic solvent, wherein the polyurethane resin (A) is prepared using a polyol and a polyisocyanate compound as reactive raw materials, and contains at least a polyester polyol (a1) and a diol (a2) having 1 to 20 carbon atoms as the polyols, and the polyester polyol (a1) is prepared using two or more types of diols as reactive raw materials, and the diol essentially contains ethylene glycol.
[0009] The present invention also relates to a liquid ink composition containing a binder resin containing a polyurethane resin (A) and an organic solvent, wherein the polyurethane resin (A) is made from a polyol and a polyisocyanate compound as reaction raw materials, and contains at least a polyester polyol (a1) and a diol (a2) having 1 to 20 carbon atoms as the polyols, and the polyester polyol (a1) is made from two or more types of diols as reaction raw materials, and the diol essentially contains ethylene glycol, and the liquid ink composition is printed on a substrate.
[0010] The present invention also relates to a liquid ink composition containing a binder resin containing a polyurethane resin (A) and an organic solvent, wherein the polyurethane resin (A) is made from a polyol and a polyisocyanate compound as reaction raw materials, and contains at least a polyester polyol (a1) and a diol (a2) having 1 to 20 carbon atoms as the polyols, and the polyester polyol (a1) is made from two or more types of diols as reaction raw materials, and the diol essentially contains ethylene glycol, and the liquid ink composition includes a laminate or package including a printed matter obtained by printing on a substrate. Effect of the Invention
[0011] According to the present invention, it is possible to provide a liquid ink composition which does not precipitate at low temperatures, can be applied to a wide variety of films, and has excellent laminate strength. The liquid ink composition of the present invention can achieve excellent laminate strength in both extrusion lamination and dry lamination. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] (Definition of words) In the present invention, the liquid printing ink composition refers to a liquid ink, such as gravure ink or flexographic ink, that is applied to a printing method using a printing plate, and is preferably gravure ink or flexographic ink. The printing liquid ink of the present invention does not contain an active energy curable component, i.e., it is an active energy ray non-reactive liquid ink.
[0013] In the following description, all "ink" refers to "printing ink." Furthermore, all "parts" refer to "parts by mass," "total amount of ink" refers to the total amount of ink including all volatile components such as organic solvents, and "total amount of ink solids" refers to the total amount of only non-volatile components, excluding volatile components.
[0014] The present invention relates to an ink composition for flexible packaging laminates, which contains a binder resin containing a polyurethane resin (A) and an organic solvent.
[0015] (Polyurethane resin (A)) The polyurethane resin (A) used in the liquid ink composition of the present invention is obtained by reacting a polyol, a polyisocyanate, a chain extender, and, if necessary, a monovalent active hydrogen compound.
[0016] The polyester polyol, which is a reaction raw material for the polyurethane resin (A) used in the liquid ink composition of the present invention, is a polyester polyol (a1) that uses two or more diols as reaction raw materials and contains ethylene glycol as an essential diol.
[0017] The polyester polyol (a1) may be, for example, one obtained by a known esterification reaction between two or more diols and a polybasic acid, and is preferably a polyester polyol obtained by dehydration condensation or polymerization of two or more low molecular weight diols and a polybasic carboxylic acid or anhydride thereof. The polyester polyol can increase the laminate strength by introducing an ester group to increase the cohesive energy.
[0018] As the diol, two or more kinds of diols including ethylene glycol and a diol having 3 or more carbon atoms are used. Examples of the diol having 3 or more carbon atoms include glycols such as propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol, 1,4-cyclohexanediol, and 1,4-cyclohexanedimethanol; 2-methyl-1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,2-butanediol, 1,3-butanediol, 2-butyl-2-ethyl- Glycols having a branched structure such as 1,3-propanediol, 1,2-propanediol, 2-methyl-1,3-propanediol, neopentyl glycol, 2-isopropyl-1,4-butanediol, 2,4-dimethyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, 2-ethyl-1,3-hexanediol, 2-ethyl-1,6-hexanediol, 3,5-heptanediol, and 2-methyl-1,8-octanediol; trimethylolpropane, trimethylolethane, pentaerythritol, and sorbitol can be used. Diols having 3 or more carbon atoms may be used alone or in combination. Among them, propylene glycol and 1,4-butanediol are preferably used.
[0019] By using ethylene glycol and a diol having 3 or more carbon atoms in combination as the polyester polyol (a1), low-temperature crystallization of the resin can be prevented and the laminate strength can be improved.
[0020] Examples of the polybasic acid that can be used include succinic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, maleic anhydride, fumaric acid, 1,3-cyclopentanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, phthalic acid, and anhydrides of these acids. These polybasic acids may be used alone or in combination of two or more kinds.
[0021] In addition to those obtained using two or more diols as reaction raw materials, the polyester polyol (a1) may contain various known polyester polyols that are generally used in the production of polyurethane resins, such as polyester polyols obtained by ring-opening polymerization of cyclic ester compounds, for example lactones such as polycaprolactone, polyvalerolactone, and poly(β-methyl-γ-valerolactone).
[0022] The polyester polyol (a1) has a number average molecular weight of preferably 1,500 or more and 8,000 or less, more preferably 1,600 or more and 7,000 or less, and even more preferably 1,800 or more and 6,000 or less.
[0023] In the present invention, the number average and weight average molecular weights are values measured by gel permeation chromatography (GPC) under the following conditions.
[0024] Measurement equipment: High-speed GPC equipment (Tosoh Corporation "HLC-8220GPC") Column: The following columns manufactured by Tosoh Corporation were used, connected in series.
[0025] "TSKgel G5000" (7.8mm I.D. x 30cm) x 1 "TSKgel G4000" (7.8mm I.D. x 30cm) x 1 "TSKgel G3000" (7.8mm I.D. x 30cm) x 1 "TSKgel G2000" (7.8mmI.D. x 30cm) x 1 Detector: RI (differential refractometer) Column temperature: 40℃ Eluent: tetrahydrofuran (THF) Flow rate: 1.0mL / min Injection volume: 100 μL (sample concentration 0.4% by mass in tetrahydrofuran solution) Standard sample: A calibration curve was prepared using the following standard polystyrene. [Standard polystyrene] "TSKgel Standard Polystyrene A-500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-1000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-2500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-5000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-1" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-2" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-4" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-10" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-20" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-40" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-80" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-128" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-288" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-550" manufactured by Tosoh Corporation The polyurethane resin (A) further contains a diol (a2) having 1 to 20 carbon atoms as a polyol, which is a reaction raw material. By containing the diol (a2) having 1 to 20 carbon atoms, the extrusion laminate strength can be improved.
[0026] The diol (a2) having 1 to 20 carbon atoms is preferably a glycol having 2 to 15 carbon atoms, more preferably a glycol having 3 to 10 carbon atoms. Specific examples include ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol, 1,4-cyclohexanediol, and 1,4-cyclohexanedimethanol. Of these, it is preferable to use 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, and diethylene glycol.
[0027] From the viewpoints of improving laminate strength and maintaining blocking properties, the mass ratio of the polyester polyol (a1) to the diol (a2) having 1 to 20 carbon atoms is preferably in the range of 99.5:0.5 to 70:30, more preferably 99.5:0.5 to 80:20, and even more preferably 99:1 to 85:15.
[0028] On the other hand, in order to improve boiling retort resistance, it is preferable that the polyurethane resin (A) does not contain a polyether polyol as a reaction raw material.
[0029] Examples of diisocyanate compounds used in polyurethane resins include various known aromatic diisocyanates, aliphatic diisocyanates, and alicyclic diisocyanates that are generally used in the production of polyurethane resins. For example, 1,5-naphthylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-diphenyldimethylmethane diisocyanate, 4,4'-dibenzyl isocyanate, dialkyldiphenylmethane diisocyanate, tetraalkyldiphenylmethane diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, tolylene diisocyanate, butane-1,4-diisocyanate, hexamethylene diisocyanate, isopropylene diisocyanate, methylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, cyclohexane-1,4-diisocyanate, cyclohexane-2,4-di ... ,4-diisocyanate, xylylene diisocyanate, isophorone diisocyanate, dimeryl diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, 1,3-bis(isocyanatemethyl)cyclohexane, methylcyclohexane diisocyanate, norbornane diisocyanate, m-tetramethylxylylene diisocyanate, 4,4-diphenylmethane diisocyanate, tolylene diisocyanate, bis-chloromethyl-diphenylmethane-diisocyanate, 2,6-diisocyanate-benzyl chloride, and dimer diisocyanate in which the carboxyl group of dimer acid is converted to an isocyanate group, etc. These diisocyanate compounds can be used alone or in combination of two or more kinds.
[0030] Compounds having amino groups used in forming polyurethane polyurea resin include chain extenders for extending the molecular weight of urethane prepolymers and end blocking agents for stopping the reaction of polyurethane polyurea resins. Chain extenders include ethylenediamine, propylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, isophoronediamine, dicyclohexylmethane-4,4'-diamine, etc., as well as amines having hydroxyl groups in the molecule such as 2-hydroxyethylethylenediamine, 2-hydroxyethylpropyldiamine, 2-hydroxyethylpropylenediamine, di-2-hydroxyethylethylenediamine, di-2-hydroxyethylenediamine, di-2-hydroxyethylpropylenediamine, 2-hydroxypropylethylenediamine, di-2-hydroxypropylethylenediamine, and di-2-hydroxypropylethylenediamine. These chain extenders can be used alone or in combination of two or more.
[0031] In addition, a monovalent active hydrogen compound can be used as a terminal blocking agent for the purpose of stopping the reaction. Examples of such compounds include dialkylamines such as di-n-butylamine, amines having a hydroxyl group in the molecule such as monoethanolamine and diethanolamine, and alcohols such as ethanol and isopropyl alcohol. Furthermore, when it is particularly desired to introduce a carboxyl group into the polyurethane resin, amino acids such as glycine and L-alanine can be used as a reaction stopper. These terminal blocking agents can be used alone or in combination of two or more.
[0032] The polyurethane resin (A) preferably contains a raw material derived from a biomass raw material as the above-mentioned reaction raw material. In order to obtain a more environmentally friendly ink, it is desirable that the ratio of raw materials derived from biomass raw materials in the polyurethane resin (A) is high. For example, in the polyurethane resin (A) of the present invention, it is preferable that at least one or more raw materials constituting the polyester polyol, which is a reaction raw material, are biomass. More specifically, "at least one or more raw materials constituting the polyester polyol are biomass" means that at least a part of the total carbon atoms constituting the polyester polyol contains carbon atoms derived from biomass. And, as described above, when the polyester polyol is a compound obtained by dehydration condensation or polymerization of a low molecular weight polyol and a polyvalent carboxylic acid or an anhydride thereof, it means that the low molecular weight polyol and / or the polyvalent carboxylic acid or the anhydride thereof is biomass (in other words, the total carbon atoms in the low molecular weight polyol and / or the polyvalent carboxylic acid or the anhydride thereof contain carbon atoms derived from biomass). Similarly, "at least one or more components constituting a polyether polyol or their raw materials are biomass" means that at least a part of the total carbon atoms constituting the polyether polyol contains carbon atoms derived from biomass.
[0033] Biomass refers to organic resources derived from plants and animals that can be recycled into energy or materials (e.g. agricultural, forestry and fishery products or parts of them, rice straw, rice husks, food waste, livestock excrement, wood chips, etc.), and excludes fossil fuels such as petroleum and coal.
[0034] For example, when the polyester polyol is composed of biomass, it is preferable that the polyvalent carboxylic acid or anhydride thereof, which is the raw material of the polyester polyol, contains carbon atoms derived from the biomass.
[0035] Examples of polycarboxylic acids containing carbon atoms derived from biomass include adipic acid (e.g., adipic acid obtained using a microorganism, see, for example, International Publication No. WO 2012 / 137771), azelaic acid (e.g., azelaic acid obtained by ozonolysis of oleic acid isolated from olive oil), sebacic acid (e.g., sebacic acid obtained by a method of treating ricinoleic acid obtained from castor oil with alkali at high temperature, see, for example, JP-A-2001-511809), dodecanedicarboxylic acid, maleic anhydride (e.g., maleic anhydride obtained by the method of WO 2016 / 198744), fumaric acid (e.g., fumaric acid obtained from corn cobs, etc. For example, see International Publication No. WO 2011 / 059013), succinic acid (succinic acid obtained by hydrogenating the fumaric acid), 1,4-butanediol (1,4-butanediol acid obtained by hydrogenating the fumaric acid), 1,3-cyclopentanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, phthalic acid (obtained by the method described in International Publication No. WO 2014 / 043468 or JP-T-2019-507757), anhydrides of these acids, etc. can be used as biomass-derived raw materials, and these polybasic acids may be used alone or in combination of two or more. In addition, various alcohols derived from biomass known as low molecular weight polyols may be used.
[0036] Furthermore, the polyether polyol itself or its raw material may be biomass. For example, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, etc. may be used.
[0037] To obtain a more environmentally friendly ink, it is desirable for the urethane resin to have a high ratio of biomass. For example, when biomass is used as the reaction raw material polyester polyol (b3) in the urethane resin (A), the ratio of biomass-derived solid components in the polyester polyol (b3) is preferably 30% by mass or more, more preferably 40% by mass or more, and even more preferably 50% by mass or more.
[0038] For example, when the polyester polyol is a compound obtained by dehydration condensation or polymerization using a low molecular weight polyol from biomass and / or a polycarboxylic acid from biomass or an anhydride thereof, the total content (solid content) of the low molecular weight polyol residues from biomass and the polycarboxylic acid from biomass or anhydride residues thereof in the polyester polyol is preferably 30 mass% or more, more preferably 40 mass% or more, and even more preferably 50 mass% or more.
[0039] The proportion of the biomass-derived solid component in the polyester polyol can be calculated from the charged amount.
[0040] The lower limit of the biomass carbon content (%) of the polyurethane resin (solid content) of this embodiment is preferably 30% or more, 33% or more, 35% or more, 37% or more, 40% or more, 45% or more, 48% or more, and 50% or more in this order. On the other hand, the upper limit of the biomass carbon content (%) is preferably 100% or less, 90% or less, 80% or less, 73% or less, and 68% or less in this order. The upper and lower limits can be arbitrarily combined. For example, the preferred range of the biomass carbon content (%) of the urethane resin (solid content) is preferably 30% or more, more preferably 30% or more and 90% or less, even more preferably 32% or more and 80% or less, and even more preferably 42% or more and 73% or less. When the biomass carbon content (%) of the urethane resin is 10% or more, the effect of reducing the environmental load can be exhibited.
[0041] The lower limit of the biomass carbon content (%) of the liquid ink composition (solid content) of this embodiment is preferably 30% or more, 33% or more, 35% or more, 37% or more, 40% or more, 45% or more, 48% or more, and 50% or more in this order. On the other hand, the upper limit of the biomass carbon content (%) is preferably 100% or less, 90% or less, 80% or less, 73% or less, and 68% or less in this order. The upper and lower limits can be arbitrarily combined. For example, the preferred range of the biomass carbon content (%) of the ink composition (solid content) for flexible packaging lamination is preferably 30% or more, more preferably 30% or more and 90% or less, even more preferably 32% or more and 80% or less, and even more preferably 42% or more and 73% or less. When the biomass carbon content (%) of the urethane resin is 30% or more, the effect of reducing the environmental load can be exhibited.
[0042] In this specification, "biomass carbon content (%)" refers to the radioactive carbon ( 14 The content ratio (pMC%) of C) is multiplied by the correction ratio of 0.93, and when the correction value is 100% or more, it is regarded as 100%.
[0043] In this specification, radiocarbon 14 The content ratio (pMC%) of carbon (C) indicates the carbon concentration (mass ratio) of the biomass-derived component, and is related to the so-called blending ratio of biomass. More specifically, radiocarbon ( 14 C) Radiocarbon obtained by the measurement method ( 14 C) content ratio. 14 C) has a half-life of 5730 years, and nitrogen ( 14 It is known that radioactive carbon ( 14 C) Carbon dioxide 14 After being oxidized to CO2 and dispersed into the atmosphere, it is taken up by animals and plants in the food chain, and disappears according to its half-life as it circulates through the environment via the food chain.14 C) The measurement method is that fossil fuels are radiocarbon ( 14 C), and biomass (or biological carbon) is essentially free of radioactive carbon ( 14 C) in the carbon contained in biomass (or living organisms), 14 C) Ratio to radiocarbon ( 14 C) content (pMC%). 14 The higher the ratio of radioactive carbon (pMC%), the less fossil fuels are used, which can reduce the environmental impact. 14 The value of the carbon content ratio (pMC%) of carbon dioxide (CO2) is related to the index showing the blend ratio of biomass, which is a renewable, biologically derived organic resource (=biomass carbon content (%)).
[0044] The radioactive carbon ( 14 By measuring the ratio of radioactive carbon (C) in the polyurethane resin (solid content) or the liquid ink composition (solid content), the ratio of carbon derived from biomass can be calculated. In the present disclosure, the radioactive carbon (C) in the polyurethane resin (solid content) or the liquid ink composition (solid content) is calculated by the following formula (1) or (2) using the method described in the Examples section below. 14 C) content (pMC%) of the polyurethane resin (solid content) or the liquid ink composition (solid content) was calculated as shown in the following formula (3). 14 The biomass carbon content (pMC%) was multiplied by 0.93 to obtain the biomass carbon content (%), taking into account the effects of atmospheric nuclear testing from 1950 to the present.
[0045] Formula (1): Radiocarbon ( 14 C) content ratio (pMC%) = [{Radioactive carbon in urethane resin (B) (solid content) ( 14 C) ÷ Carbon in urethane resin (solid content) ( 12 C)} / {Radiocarbon of standard material ( 14 C) / Standard Carbon ( 12 C)}×100] Formula (2): Radiocarbon ( 14 C) content ratio (pMC%) = [{radioactive carbon ( 14 C) ÷ Carbon ( 12 C)} / {Radiocarbon of standard material ( 14 C) / Standard Carbon ( 12 C)}×100] (In the above formulas (1) and (2), the standard substance used was oxalic acid (SRM4990C) supplied by the National Institute of Standards and Technology as a standard substance for dating, which was converted to graphite using the same pretreatment method as that used for the measurement graphite described in the Examples section below.) Formula (3): Biomass carbon content (%) = Radioactive carbon (%) calculated from the above formula (1) or (2) 14 C) content ratio (pMC%) x 0.93 In addition, radioactive carbon ( 14 C), which produces about 1.5 times the usual amount of radioactive carbon ( 14 C) has been observed. However, it has gradually decreased over time, and the current value is around 107.5 (pMC%). Therefore, in this disclosure, as in the ASTM D6866 standard, radiocarbon ( 14 The biomass carbon content (%) is defined as the content ratio (pMC%) of carbon (C) multiplied by 0.93 (=100 / 107.5). However, even when the method using the above formula (3) is adopted, there are cases where a value of 100% or more is calculated. Therefore, in this disclosure, as in the ASTM standard, if the value of the biomass carbon content (%) is 100% or more, it is considered to be 100%.
[0046] In this embodiment, radiocarbon ( 14 The concentration of C is measured by accelerator mass spectrometry (AMS), which combines a tandem accelerator and a mass spectrometer, to measure the isotopes of the carbon atoms (specifically, 12 C, 13C, 14 C is one example. ) is measured using a method in which the atomic mass difference is used to physically separate them using an accelerator, and the abundance of each atom of the isotope is measured.
[0047] The samples to be analyzed are polyurethane resin (solid content) or liquid ink composition (solid content), and require pretreatment. Specifically, as described in the Examples section below, the carbon contained in these samples is oxidized and converted into carbon dioxide. The carbon dioxide obtained is then separated from water and nitrogen, reduced, and converted into graphite, which is solid carbon. The graphite obtained is used as a measurement sample, and Cs is added to the sample. + The carbon ions are accelerated using a 3MV tandem accelerator, and the negative ions are converted to positive ions. The negative ions are then converted to positive ions using a mass analysis magnet. 12 C 3+ , 13 C 3+ , 14 C 3+ Separating the traveling orbit of 14 C 3+ In the accelerator mass spectrometry of this embodiment, a method of performing measurements using an electrostatic analyzer is adopted.
[0048] The carbon isotopes contained in the graphite obtained from the pretreated sample 12 C. 13 C and 14 C is accelerated at the same speed and its flight path is bent by the magnetic field of the mass analysis electromagnet. 12 C. 13 C is on the inside, the heaviest 14 C flies on the outermost side of the bend. 12 C. 13 Since the amount of C is large, it is detected as a current by a Faraday cup detector. 14 C are counted one by one by an ionization chamber type ion detector.
[0049] The polyurethane resin (A) used in the liquid ink composition of the present invention is obtained by reacting a polyol, a polyisocyanate, a chain extender, and, if necessary, a monovalent active hydrogen compound. For example, the polyester polyol and the polyol used in combination with a diisocyanate compound are reacted in a ratio in which the isocyanate group is in excess to obtain a prepolymer having an isocyanate group at the end, and the obtained prepolymer is reacted with a chain extender and / or a terminal blocking agent in a suitable solvent, i.e., an ester solvent such as ethyl acetate, propyl acetate, or butyl acetate, which is usually used as a solvent for liquid ink; a ketone solvent such as acetone, methyl ethyl ketone, or methyl isobutyl ketone; an alcohol solvent such as methanol, ethanol, isopropyl alcohol, or n-butanol; a hydrocarbon solvent such as toluene, xylene, methylcyclohexane, or ethylcyclohexane; or a mixture of these solvents, in a two-step method, or a one-step method in which the polyester polyol and the polyol used in combination with the diisocyanate compound, the chain extender, and / or the terminal blocking agent are reacted at once in a suitable solvent among the above. Among these methods, the two-stage method is preferred to obtain a uniform polyurethane resin (A). When producing the polyurethane resin (A) by the two-stage method, it is preferred to react the chain extender and / or the terminal blocking agent so that the total (equivalent ratio) of the amino groups is 1 / 0.9 to 1.3. When the equivalent ratio of the isocyanate group to the amino group is less than 1 / 1.3, the chain extender and / or the terminal blocking agent remain unreacted, which may cause the polyurethane resin to yellow or emit an odor after printing.
[0050] The weight average molecular weight of the polyurethane resin (A) thus obtained is preferably within the range of 15,000 to 150,000. More preferably, it is within the range of 20,000 to 130,000. If the weight average molecular weight of the polyurethane resin (A) is 15,000 or more, the blocking resistance of the obtained ink composition, the strength of the printed film, oil resistance, etc. are unlikely to decrease, and if it is 150,000 or less, the viscosity of the obtained ink composition does not become too high, and there is no problem in production and work efficiency. The weight average molecular weight of the polyurethane resin (A) is a value obtained by measuring in the same manner as the number average molecular weight of the polyester polyol.
[0051] The polyurethane resin (A) can be used without any particular limitation as long as it has the above-mentioned composition, but among these, those containing active hydrogen-containing functional groups, such as hydroxyl groups, primary or secondary amino groups, etc. in the urethane resin are preferred because crosslinking between the urethane resin and the blocked isocyanate proceeds smoothly and the resulting printed ink layer becomes strong. Even if the urethane resin does not contain active hydrogen-containing functional groups, the ink layer can be heated at a high temperature to obtain the same results as when a urethane resin containing active hydrogen is used.
[0052] The urethane bond concentration of the polyurethane resin (A) is preferably 0.6 mmol / g or more, more preferably 0.7 mmol / g or more, and even more preferably 0.8 or more. When the urethane bond concentration is 0.6 mmol / g or more, the extrusion laminate strength is particularly excellent. On the other hand, the upper limit of the urethane bond concentration is preferably 2.5 mmol / g, and more preferably 2.0 mmol / g. The urethane bond concentration can be calculated by the following formula (1). Urethane bond concentration = {(W1 × OH1 + W2 × OH2 + + W i ×OH i )×1000} / (56100×S) Equation (1) In formula (1), each is as follows. W1: Weight of polyol 1 OH1: hydroxyl value of polyol 1 W2: Weight of polyol 2 OH2: Hydroxyl value of polyol 2 W i : weight of polyol i OH i : Hydroxyl value of polyol i S: Weight of urethane resin solids In addition, the polyurethane resin (A) has a urea bond, and the urea bond concentration in the polyurethane resin (A) is preferably 1.5 mmol / g or less. If the urea bond concentration is within this range, the boiling retort resistance of the ink film can be improved without decreasing the extrusion laminate strength. The preferred range of the urea bond concentration is 0.1 to 1.2 mmol / g, and more preferably 0.2 to 1.0 mmol / g.
[0053] The urea binding concentration here can be calculated by the following formula (1). Urea bond concentration={(X1 / M1+X2 / M2+···+X i / M i )×2-(W1×OH1+W2×OH2+···+W i ×OH i ) / 56100}×1000 / S formula (1) In formula (1), the symbols are as follows: X1: Weight of diisocyanate compound 1 M1: Molecular weight of diisocyanate compound 1 X2: Weight of diisocyanate compound 2 M2: Molecular weight of diisocyanate compound 2 X i : Weight of diisocyanate compound i M i : Molecular weight of diisocyanate compound i W1: Weight of polyol 1 OH1: hydroxyl value of polyol 1 W2: Weight of polyol 2 OH2: Hydroxyl value of polyol 2 W i : weight of polyol i OH i : Hydroxyl value of polyol i S: Weight of urethane resin solids The content of the polyurethane resin (A) used in the liquid ink composition of the present invention is preferably 4% by mass or more based on the total amount of the composition from the viewpoint of sufficient adhesion of the ink to the substrate, and 35% by mass or less from the viewpoint of appropriate ink viscosity and work efficiency during ink production and printing, more preferably in the range of 10 to 30% by mass. The proportion of the polyurethane resin (A) based on the total resin solid content of the liquid printing ink is preferably in the range of 30 to 100% by mass, more preferably in the range of 40 to 90% by mass.
[0054] (Other resins) Furthermore, the liquid ink composition of the present invention may contain other known resins in addition to the polyurethane resin (A). Examples of the other resins include urethane resins (B) other than the polyurethane resin (A), vinyl chloride-vinyl acetate copolymer resins, cellulose resins, polyester resins, rosin resins, acrylic resins, polyamide resins, chlorinated polypropylene resins, ethylene-vinyl acetate copolymer resins, vinyl acetate resins, alkyd resins, polyvinyl chloride resins, ketone resins, cyclized rubbers, chlorinated rubbers, butyral resins, and petroleum resins. Among these, it is preferable to contain a polyurethane resin (B) other than the polyurethane resin (A) and a vinyl chloride-vinyl acetate copolymer resin. In addition, two or more kinds of polyurethane resins (B) other than the polyurethane resin (A) may be contained. The content of the other resins that can be used in combination with the polyurethane resin (A) is preferably 0.5 to 40% by weight, more preferably 10 to 30% by weight, based on the total weight of the ink.
[0055] As the polyurethane resin (B) other than the polyurethane resin (A), it is preferable to use a polyurethane resin (B) having a urethane bond concentration lower than that of the polyurethane resin (A) in combination. By using the polyurethane resin (A) in combination with the polyurethane resin (B), it is possible to improve printability. The urethane bond concentration of the polyurethane resin (B) is preferably in the range of 0.3 to 0.8 mmol / g, and more preferably 0.3 mmol / g or more and less than 0.6 mmol / g.
[0056] When polyurethane resin (B) is used in combination, its content is preferably in the range of 1 to 50% and more preferably in the range of 10 to 40% by mass based on the total resin solid content of the liquid printing ink. Also, the mass ratio of polyurethane resin (A) to polyurethane resin (B) in terms of solid components is preferably polyurethane resin (A):polyurethane resin (B)=40:60 to 95:5 and more preferably 50:50 to 90:10.
[0057] When the liquid ink composition contains a plurality of polyurethane resins, the urethane bond concentration of the entire urethane resin components is preferably 0.6 mmol / g or more, more preferably 0.7 mmol / g or more, and even more preferably 0.8 mmol / g or more, from the viewpoint of improving the extrusion laminate strength. On the other hand, the upper limit of the urethane bond concentration is preferably 2.0 mmol / g, and more preferably 1.5 mmol / g.
[0058] The polyurethane resin (B) is obtained by reacting a polyol, a polyisocyanate, a chain extender, and, if necessary, a monovalent active hydrogen compound. The polyol may be one or more selected from the group consisting of polycarbonate or a polyoxyalkylene compound having a structural unit of 3 to 4 carbon atoms, polyester polyol, polyether polyol, and aromatic polyol compound, and may be a combined polyol added if necessary. The polyol is preferably a combination of a polyester polyol and a polyether polyol, and preferably contains 1 to 30 parts of a polyether polyol resin having a number average molecular weight of 100 to 3500 per 100 parts of the polyurethane resin.
[0059] The polyurethane resin (B) preferably contains a raw material derived from a biomass raw material as the above-mentioned reaction raw material, similarly to the polyurethane resin (A). For example, in the polyurethane resin (B) of the present invention, it is preferable to use a raw material derived from a biomass raw material as the polyester polyol, which is a reaction raw material.
[0060] The vinyl chloride-vinyl acetate copolymer resin is not particularly limited and any known vinyl chloride-vinyl acetate copolymer resin can be used, among which a hydroxyl group-containing vinyl chloride-vinyl acetate copolymer resin is preferred, and a hydroxyl group-containing vinyl chloride-vinyl acetate copolymer resin having a hydroxyl group with a hydroxyl value of 50 to 200 mgKOH / g and a content ratio of vinyl chloride component in the copolymer resin of 80 to 95% by weight is even more preferred.
[0061] Hydroxyl-containing vinyl chloride / vinyl acetate copolymer resins can be obtained in two ways. One is obtained by copolymerizing vinyl chloride monomer, vinyl acetate monomer, and vinyl alcohol in an appropriate ratio. The other is obtained by copolymerizing vinyl chloride and vinyl acetate, and then partially saponifying the vinyl acetate. The properties of the resin coating and the resin dissolution behavior of the vinyl chloride / vinyl acetate copolymer resins with hydroxyl groups are determined by the monomer ratio of vinyl chloride, vinyl acetate, and vinyl alcohol. That is, vinyl chloride gives the resin coating strength and hardness, vinyl acetate gives adhesion and flexibility, and vinyl alcohol gives good solubility in polar solvents.
[0062] In addition, as the monomer ratio of the vinyl chloride-vinyl acetate copolymer resin having a hydroxyl group, for example, 80 to 95 parts by mass of vinyl chloride is more preferable because it balances blocking resistance and adhesiveness with 100 parts by mass of the vinyl chloride-vinyl acetate copolymer resin having a hydroxyl group. If it is 80 parts by mass or more, the toughness of the resin coating can be maintained and blocking resistance can be ensured. If it is 95 parts by mass or less, the resin coating does not become too hard and adhesiveness is unlikely to decrease. In addition, the hydroxyl value obtained from the vinyl alcohol is preferably 50 to 200 mgKOH / g. If it is 50 mgKOH / g or more, the solubility in polar solvents is good and the printability is easily stabilized. If it is 200 mgKOH / g or less, the lamination suitability can be maintained well.
[0063] When a vinyl chloride-vinyl acetate copolymer resin is used in combination, its content is preferably in the range of 1 to 30% by mass, more preferably in the range of 5 to 20% by mass, based on the total resin solid content of the liquid printing ink.
[0064] The liquid ink composition of the present invention preferably contains, as the resin component, for example, polyurethane resin (A) / polyurethane resin (B), polyurethane resin (A) / vinyl chloride / vinyl acetate copolymer resin, or polyurethane resin (A) / polyurethane resin (B) / vinyl chloride / vinyl acetate copolymer resin.
[0065] (Organic solvent) Examples of solvents that can be used in the liquid printing ink of the present invention include aromatic organic solvents, ketone solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, ester solvents such as ethyl acetate, n-propyl acetate, butyl acetate, and propylene glycol monomethyl ether acetate, and alcohol solvents such as n-propanol, isopropanol, n-butanol, and propylene glycol monomethyl ether, and these can be used alone or in a mixture of two or more. In recent years, from the viewpoint of the working environment, it is desirable not to use aromatic solvents such as toluene and xylene, and ketone solvents.
[0066] (water) Water may be added to the liquid printing ink of the present invention together with the organic solvent as a volatile component. By adding water, the drying property of the ink can be controlled, and in particular in gravure printing, the gradation part, which is characterized by a small amount of ink transfer, can be beautifully reproduced. The amount of water added is preferably in the range of 0.3 to 10 mass% of the total amount of the ink composition in terms of good printability. If the amount of water added is 0.3 mass% or more, the reproducibility of the gradation part tends to be good without decreasing the effect of suppressing the drying of the ink. If the amount of water added is 10 mass% or less of the total amount of the ink composition, the ink stability can be suppressed from decreasing. In addition, by adding such water, it is possible to reduce the organic solvent component used, which leads to environmental friendliness. Water may be added to the organic solvent in advance to form a water-containing organic solvent, or a specific amount may be added separately.
[0067] (Coloring agent) Colorants include organic and inorganic pigments and dyes used in general inks, paints, and recording materials. Organic pigments include azo, phthalocyanine, anthraquinone, perylene, perinone, quinacridone, thioindigo, dioxazine, isoindolinone, quinophthalone, azomethine azo, dictopyrrolopyrrole, and isoindoline pigments. Copper phthalocyanine is preferably used for indigo ink, and CI Pigment No. Yellow 83 is preferably used for transparent yellow ink from the viewpoints of cost and light resistance.
[0068] Examples of inorganic pigments include carbon black, titanium oxide, zinc oxide, zinc sulfide, barium sulfate, calcium carbonate, chromium oxide, silica, red iron oxide, aluminum, and mica. Also, a glittering pigment (Metashine; Nippon Sheet Glass Co., Ltd.) in which a metal or metal oxide is coated on a base material of glass flakes or agglomerated flakes can be used. From the viewpoint of cost and coloring power, it is preferable to use titanium oxide for white ink, carbon black for black ink, aluminum for gold and silver ink, and mica for pearl ink. It is preferable that titanium oxide has a treatment layer containing at least alumina and / or silica on the surface. In titanium oxide surface-treated with alumina and / or silica, silica is generally used for the purpose of adjusting the acid-base state of the titanium oxide surface and for imparting durability to the resulting ink / paint film, and alumina is used to improve the wetting of titanium oxide during dispersion. Examples of surface treatment methods for titanium oxide include aqueous treatment and gas-phase treatment. The aluminum is in powder or paste form, but it is preferably used in paste form from the standpoint of ease of handling and safety. Whether leafing or non-leafing aluminum is used is appropriately selected from the standpoint of brightness and concentration.
[0069] The colorant is preferably contained in an amount sufficient to ensure the concentration and coloring power of the ink, i.e., 1 to 50% by weight based on the total weight of the ink. The colorant may be used alone or in combination of two or more kinds.
[0070] (Other additives) In the present invention, the composition may further contain, if necessary, a co-used resin, an extender pigment, a pigment dispersant, a leveling agent, an antifoaming agent, a wax, a plasticizer, an infrared absorbing agent, an ultraviolet absorbing agent, an aromatic agent, a flame retardant, and the like.
[0071] In order to stably disperse the pigment in an organic solvent, the above resin alone can be used, but a dispersant can also be used in combination to further stably disperse the pigment. As the dispersant, anionic, nonionic, cationic, amphoteric surfactants can be used. For example, comb-structured polymer compounds obtained by adding polyester to polyethyleneimine, or alkylamine derivatives of α-olefin maleic acid polymers can be used. Specific examples include the Solspers series (ZENECA), Ajisper series (Ajinomoto), and Homogenol series (Kao). In addition, the BYK series (BYK-Chemie), EFKA series (EFKA), and the like can be appropriately used. The dispersant is preferably contained in the ink in an amount of 0.05% by weight or more based on the total weight of the ink from the viewpoint of storage stability of the ink, and 5% by weight or less from the viewpoint of lamination suitability, and more preferably in the range of 0.1 to 2% by weight.
[0072] The liquid ink composition of the present invention can be produced by dissolving and / or dispersing a resin, a colorant, etc. in an organic solvent. Specifically, a pigment dispersion is produced by dispersing a pigment in an organic solvent with a polyurethane resin, and other compounds, etc., are added to the obtained pigment dispersion as necessary to produce an ink.
[0073] The particle size distribution of the pigment in the pigment dispersion can be adjusted by appropriately adjusting the size of the grinding media of the dispersing machine, the packing rate of the grinding media, the dispersion treatment time, the discharge speed of the pigment dispersion, the viscosity of the pigment dispersion, etc. As the dispersing machine, for example, a commonly used roller mill, ball mill, pebble mill, attritor, sand mill, etc. can be used.
[0074] When air bubbles or unexpectedly large particles are contained in the ink, they degrade the quality of the printed matter, so it is preferable to remove them by filtration, etc. As the filter, a conventionally known filter can be used.
[0075] The viscosity of the ink produced by the above method is preferably in the range of 10 mPa s or more from the viewpoint of preventing sedimentation of the pigment and adequately dispersing it, and 1000 mPa s or less from the viewpoint of workability during ink production and printing. The above viscosity is measured at 25°C using a Tokimec B-type viscometer.
[0076] The viscosity of the ink can be adjusted by appropriately selecting the types and amounts of raw materials used, such as polyurethane resin, colorant, organic solvent, etc. The viscosity of the ink can also be adjusted by adjusting the particle size and particle size distribution of the pigment in the ink.
[0077] When a colorant is used in the liquid ink composition of the present invention, the hues are determined according to the type of colorant used, and there are five process basic colors, yellow, red, indigo, black, and white, and three process gamut colors, red (orange), grass (green), and purple. In addition, transparent yellow, peony, vermilion, brown, gold, silver, pearl, and a nearly transparent medium (containing an extender pigment as necessary) for adjusting color density are prepared as base colors. Ink for boil retort printing is appropriately selected in consideration of the migration property and heat resistance of the pigment. The base ink of each hue is diluted with a diluting solvent to a viscosity and concentration suitable for gravure printing or flexographic printing, and is supplied to each printing unit alone or mixed.
[0078] (Printed material) The printed matter of the present invention is a printed matter having a printed layer formed by printing the liquid printing ink of the present invention on a substrate. The liquid printing ink of the present invention has excellent adhesion to various substrates and can be used for printing on paper, synthetic paper, thermoplastic resin films, plastic products, steel plates, etc., and is useful as an ink for gravure printing using a gravure printing plate by electronic engraving intaglio or the like, or for flexographic printing using a flexographic printing plate by a resin plate or the like, but excludes ink for an inkjet method in which ink is ejected from an inkjet nozzle without using a plate.
[0079] That is, in the case of inkjet ink, ink droplets ejected from a nozzle directly adhere to a substrate to form a printed matter, whereas in the case of the liquid printing ink of the present invention, the printing ink is first adhered to and transferred to a printing plate or a printing pattern, and then the ink alone is again adhered to the substrate and dried as necessary to form a printed matter.
[0080] The film thickness of the printing ink formed by the gravure printing method or flexographic printing method using the liquid printing ink of the present invention is, for example, 10 μm or less, preferably 5 μm or less.
[0081] Examples of the substrate include films and laminates made of polyamide resins such as nylon 6, nylon 66, and nylon 46; polyester resins such as polyethylene terephthalate (hereinafter sometimes referred to as PET), polyethylene naphthalate, polytrimethylene terephthalate, polytrimethylene naphthalate, polybutylene terephthalate, and polybutylene naphthalate; biodegradable resins such as polyhydroxycarboxylic acids such as polylactic acid, and aliphatic polyester resins such as poly(ethylene succinate) and poly(butylene succinate); thermoplastic resins such as polyolefin resins such as polypropylene and polyethylene, polyimide resins, polyarylate resins, and mixtures thereof; and among these, films made of polyester, polyamide, polyethylene, and polypropylene are preferably used.
[0082] It is also preferable to use a film formed from a material containing a biomass-derived component as the substrate. Biomass films are commercially available from various companies, and known sheets such as those listed in the list of biomass certified products listed in the Japan Organics Resources Association, a general incorporated foundation, can be used.
[0083] These films may be laminated films in which multiple films are laminated together, such as a laminate in which a biomass film is laminated, or a laminate of a conventional petroleum-based film and a biomass film.
[0084] These substrate films may be unstretched or stretched films, and the manufacturing method is not limited. The thickness of the substrate film is not particularly limited, but is usually in the range of 1 to 500 μm.
[0085] These substrate films may be laminated with a vapor-deposited layer of a metal such as aluminum or a metal oxide such as silica or alumina, may use a metal foil, may be used in combination with a barrier film containing a gas barrier layer such as polyvinyl alcohol, an ethylene-vinyl alcohol copolymer, or vinylidene chloride, or may be coated with polyvinyl alcohol. By using such a film, a laminate having high barrier properties against water vapor, oxygen, alcohol, inert gases, volatile organic compounds (fragrances), etc. can be obtained. The liquid printing ink of the present invention can obtain excellent adhesion even to a vapor-deposited layer or a film that has been subjected to various coating treatments.
[0086] The printing method can be a known printing method such as gravure printing or flexographic printing, but gravure printing is particularly preferred.
[0087] In the above printing method, i.e., after the printing ink is once adhered and transferred to a printing plate or a printing pattern, only the ink is adhered again to a substrate and, if necessary, dried or cured in an oven to fix it, thereby obtaining a printed matter. The film thickness of the printing ink formed by the gravure printing method or flexographic printing method using the liquid printing ink of the present invention is, for example, 10 μm or less, preferably 5 μm or less.
[0088] The printed matter of the present invention can be preferably used on a film substrate with the above-mentioned liquid ink composition as a front printing ink, a back printing ink, or a lamination ink. When used as a front printing ink, an overprint varnish layer can be provided separately. The overprint varnish may not contain a colorant, or various pigments may be used for coloring purposes. On the other hand, when used as a back printing ink, an anchor coat varnish layer can be provided separately. In addition to the printing layer using the liquid ink composition of the present invention, another printing layer containing a colorant may be provided.
[0089] In particular, the liquid printing ink of the present invention is preferably used as an ink for lamination because of its excellent lamination strength.
[0090] (Laminate) The laminate of the present invention is obtained by laminating a plurality of substrates, and has a printed layer of the liquid printing ink of the present invention on at least one of the substrates. The substrates can be laminated by lamination using an adhesive or by extrusion lamination.
[0091] More specifically, the laminate has the following structure: (1) Base film 1 / printing layer / adhesive layer 1 / sealant film (2) Base film 1 / printed layer / adhesive layer 1 / metal-deposited unstretched film (3) Base film 1 / printed layer / adhesive layer 1 / metal-deposited stretched film (4) Transparent vapor-deposited stretched film / printed layer / adhesive layer 1 / sealant film (5) Base film 1 / printing layer / adhesive layer 1 / base film 2 / adhesive layer 2 / sealant film (6) Base film 1 / printed layer / adhesive layer 1 / metal-deposited stretched film / adhesive layer 2 / sealant film (7) Base film 1 / printed layer / adhesive layer 1 / transparent vapor-deposited stretched film / adhesive layer 2 / sealant film (8) Base film 1 / printed layer / adhesive layer 1 / metal layer / adhesive layer 2 / sealant film (9) Base film 1 / printing layer / adhesive layer 1 / base film 2 / adhesive layer 2 / metal layer / adhesive layer 3 / sealant film (10) Base film 1 / printed layer / adhesive layer 1 / metal layer / adhesive layer 2 / base film 2 / adhesive layer 3 / sealant film Examples include, but are not limited to, the above. The above "base film 1 / and printed layer" corresponds to the above printed matter having a white printed layer and a color printed layer on a film base. In the above configurations (1) to (10), a printed layer is provided on the surface of the base film 1 on the adhesive layer 1 side, but a printed layer may be provided on the surface (front surface) of the base film 1 opposite to the adhesive layer 1, or a printed layer may be provided on the base film 2.
[0092] Examples of the base film 1 used in the structure (1) include an OPP film, a PET film, and a nylon film (hereinafter also referred to as an Ny film). The base film 1 may be coated with a coating for the purpose of improving the gas barrier properties and the ink receptivity when a printing layer is provided, which will be described later. Examples of commercially available base films 1 with coatings include K-OPP films and K-PET films. Examples of sealant films include CPP films and LLDPE films.
[0093] The base film 1 used in the structures (2) and (3) can be an OPP film, a PET film, etc. As the metal-vapor-deposited unstretched film, a VM-CPP film obtained by depositing a metal such as aluminum on a CPP film can be used, and as the metal-vapor-deposited stretched film, a VM-OPP film obtained by depositing a metal such as aluminum on an OPP film can be used.
[0094] Examples of the transparent evaporated stretched film used in the structure (4) include films obtained by evaporating silica or alumina onto OPP film, PET film, nylon film, etc. For the purpose of protecting the inorganic evaporated layer of silica or alumina, a film having a coating applied onto the evaporated layer may be used. Examples of the sealant film include the same as those in the structure (1).
[0095] The base film 1 used in the structure (5) may be a PET film, etc. The base film 2 may be a nylon film, etc. The sealant film may be the same as that in the structure (1).
[0096] The base film 1 of the structure (6) may be the same as that of the structures (2) and (3). The metal-vapor-deposited stretched film may be a VM-OPP film or a VM-PET film in which a metal such as aluminum is vapor-deposited on an OPP film or a PET film. The sealant film may be the same as that of the structure (1).
[0097] The base film 1 in the structure (7) may be a PET film, etc. The transparent deposition stretched film may be the same as that in the structure (4). The sealant film may be the same as that in the structure (1).
[0098] The base film 1 in the structure (8) may be a PET film, etc. The metal layer may be an aluminum foil, etc. The sealant film may be the same as that in the structure (1).
[0099] In the structures (9) and (10), the base film 1 may be a PET film or the like. The base film 2 may be a nylon film or the like. The metal layer may be an aluminum foil or the like. The sealant film may be the same as that in the structure (1).
[0100] (adhesive layer) The adhesive layer may be formed by a known adhesive for film lamination. When laminating by extrusion lamination, a known anchor coating agent for extrusion lamination may be used as an adhesive auxiliary. When a material having gas barrier properties is used as the adhesive or anchor coating agent, a laminate having particularly excellent barrier properties can be obtained.
[0101] As an adhesive with excellent gas barrier properties, 3 g / m 2 The oxygen barrier property of the cured coating of the adhesive applied at (solid content) is 300cc / m 2 / day / atm or less, or water vapor barrier of 120g / m 2 / day. Commercially available products include the "PASLIM" series, such as PASLIM VM001 and PASLIM J350X, manufactured by DIC Corporation, and "Maxive" manufactured by Mitsubishi Gas Chemical Company.
[0102] The adhesive layer may be made of any known material without particular limitation, but preferably contains a cured product of a polyol and an isocyanate compound. When the polyol and / or isocyanate compound contains a biomass-derived component, a laminate with a high biomass content can be obtained, thereby reducing the environmental load.
[0103] In addition, the adhesive may contain an adhesion promoter, an acid anhydride, a compound having an oxygen scavenging function, a tackifier, a gas barrier adhesive stabilizer (antioxidant, heat stabilizer, ultraviolet absorber, etc.), a plasticizer, an antistatic agent, a lubricant, an antiblocking agent, a colorant, a crystal nucleating agent, etc. These various additives may be added in advance to either one or both of the polyol composition (A) and the polyisocyanate composition (B), or may be added when the polyol composition (A) and the polyisocyanate composition (B) are mixed.
[0104] The gas barrier adhesive used may be either a solvent-based or solventless type. When the gas barrier adhesive used is a solvent-based adhesive, the adhesive of the present invention is applied onto the surface of the printed layer printed on the first substrate using a roll such as a gravure roll, and the organic solvent is evaporated by heating in an oven or the like, and then the other substrate is laminated to obtain the laminate of the present invention. After lamination, it is preferable to perform an aging treatment. The aging temperature is preferably room temperature to 80°C, and the aging time is preferably 12 to 240 hours.
[0105] When the gas barrier adhesive used is a solventless type, the adhesive of the present invention, which has been preheated to about 40°C to 100°C, is applied to the printed layer surface of the first substrate using a roll such as a gravure roll, and the other substrate is immediately laminated to obtain the laminate of the present invention. After lamination, it is preferable to carry out an aging treatment. The aging temperature is preferably room temperature to 70°C, and the aging time is preferably 6 to 240 hours.
[0106] When the gas barrier adhesive is used as an adhesion promoter, the adhesion promoter of the present invention is applied to the printed layer surface printed on the first substrate using a roll such as a gravure roll, and the organic solvent is evaporated by heating in an oven or the like, and then the polymer material melted by an extruder is laminated to obtain the laminate of the present invention. As the polymer material to be melted, polyolefin resins such as low-density polyethylene resin, linear low-density polyethylene resin, and ethylene-vinyl acetate copolymer resin are preferred. The aging temperature is preferably room temperature to 70°C, and the aging time is preferably 6 to 240 hours.
[0107] The amount of gas barrier adhesive to be applied is adjusted as appropriate. For example, in the case of a solvent-based adhesive, the solid content is 1 g / m 2 More than 10g / m 2 Less than 2 g / m 2 More than 5g / m 2 Adjust the amount of adhesive applied so that it is as follows: For a solvent-free adhesive, the amount of adhesive applied is, for example, 1 g / m 2 More than 5g / m 2 Less than 1 g / m 2 More than 3g / m 2 The following is the result.
[0108] When using an adhesive as an adhesive auxiliary, the amount of application is adjusted appropriately. For example, 2 More than 2g / m 2 The solid content is as follows:
[0109] (Laminate other layers) The laminate of the present invention may be used alone or may further include other films or substrates. As the other substrates, in addition to the above-mentioned stretched film, unstretched film, and transparent vapor deposition film, porous substrates such as paper, wood, and leather can also be used. The adhesive used when bonding the other substrates may or may not be a gas barrier adhesive as described above.
[0110] <Packaging material> The printed matter and laminate of the present invention can be used as a multi-layer packaging material for the purpose of protecting food, medicines, etc. When used as a multi-layer packaging material, the layer structure can be changed depending on the contents, the environment of use, and the form of use.
[0111] The packaging material of the present invention can be obtained, for example, by using the laminate of the present invention, overlapping the surfaces of the sealant films of the laminate so that they face each other, and then heat-sealing the peripheral edge. Examples of the bag-making method include folding or overlapping the laminate of the present invention so that the surfaces of the inner layers (the surfaces of the sealant films) face each other, and heat-sealing the peripheral edge, for example, by a side seal type, a two-sided seal type, a three-sided seal type, a four-sided seal type, an envelope seal type, a grooving seal type, a pleated seal type, a flat bottom seal type, a square bottom seal type, a gusset type, or other heat seal type. The packaging material of the present invention can take various forms depending on the contents, the environment of use, and the form of use. Self-supporting packaging materials (standing pouches) and the like are also possible. Heat sealing can be performed by known methods such as bar seal, rotary roll seal, belt seal, impulse seal, high frequency seal, and ultrasonic seal.
[0112] The packaging material of the present invention is filled with contents through its opening, and the opening is then heat-sealed to produce a product using the packaging material of the present invention. The uses of the packaging material are not particularly limited, but it can be suitably used for food packaging, medicines, sanitary products, cosmetics, electronic materials, building materials, industrial materials, etc. It can also be used as a packaging material for cigarettes, disposable hand warmers, medicines, supplements, infusion packs, vacuum insulation materials, etc. EXAMPLES
[0113] The present invention will be described in more detail with reference to examples. In the following, "parts" and "%" are all based on mass. Blanks in the tables indicate that the components are not blended.
[0114] In the present invention, the weight average molecular weight (converted into polystyrene) was measured by gel permeation chromatography (GPC) using an HLC8220 system manufactured by Tosoh Corporation under the following conditions. Separation columns: four TSKgelGMHHR-N columns manufactured by Tosoh Corporation. Column temperature: 40°C. Mobile phase: tetrahydrofuran manufactured by Wako Pure Chemical Industries, Ltd. Flow rate: 1.0 ml / min. Sample concentration: 0.4% by mass. Sample injection amount: 100 microliters. Detector: differential refractometer. The viscosity was measured at 25° C. using a Tokimec B-type viscometer.
[0115] [Synthesis of polyurethane resin (A)] (Synthesis Example 1) Pu-1 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube was charged with 99.0 parts of polyester polyol (hydroxyl value: 67.6 mg KOH / g) consisting of propylene glycol and succinic acid, 1.0 parts of 1,4 butanediol (hydroxyl value: 1245.0 mg KOH / g) and 22.5 parts of isophorone diisocyanate, and reacted for 20 hours at 100 ° C. under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 2.10 mass%, and then 100.2 parts of ethyl acetate was added to the mixture to obtain a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 5.79 parts of isophorone diamine, 0.15 parts of monoethanolamine, 110.1 parts of ethyl acetate and 90.2 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45 ° C. for 5 hours to obtain a polyurethane resin solution Pu-1. The resulting polyurethane resin solution Pu-1 had a resin solid concentration of 30.2% by mass, a weight average molecular weight (Mw) of the resin solid content of 83,000, a urethane bond concentration of 1.10 mmol / g, and a urea bond concentration of 0.5 mmol / g.
[0116] (Synthesis Example 2) Pu-2 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube was charged with 95.0 parts of polyester polyol (hydroxyl value: 17.8 mg KOH / g) consisting of propylene glycol, ethylene glycol and succinic acid, 5.0 parts of 1,4 butanediol (hydroxyl value: 1245.0 mg KOH / g) and 22.5 parts of isophorone diisocyanate, and reacted at 100 ° C for 20 hours under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 2.10 mass%, and then 100.2 parts of ethyl acetate was added to the mixture to obtain a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 5.78 parts of isophorone diamine, 0.15 parts of monoethanolamine, 110.1 parts of ethyl acetate and 90.1 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45 ° C for 5 hours to obtain a polyurethane resin solution Pu-2. The resulting polyurethane resin solution Pu-2 had a resin solid concentration of 30.2% by mass, a weight average molecular weight (Mw) of the resin solid content of 83,000, a urethane bond concentration of 1.10 mmol / g, and a urea bond concentration of 0.5 mmol / g.
[0117] (Synthesis Example 3) Pu-3 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube was charged with 95.0 parts of polyester polyol (hydroxyl value: 17.8 mg KOH / g) consisting of propylene glycol, ethylene glycol and sebacic acid, 5.0 parts of 1,4 butanediol (hydroxyl value: 1245.0 mg KOH / g) and 22.5 parts of isophorone diisocyanate, and reacted at 100 ° C for 20 hours under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 2.10 mass%, and then 100.2 parts of ethyl acetate was added to the mixture to obtain a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 5.78 parts of isophorone diamine, 0.15 parts of monoethanolamine, 110.1 parts of ethyl acetate and 90.1 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45 ° C for 5 hours to obtain a polyurethane resin solution Pu-3. The resulting polyurethane resin solution Pu-3 had a resin solid concentration of 30.2% by mass, a weight average molecular weight (Mw) of the resin solid content of 83,000, a urethane bond concentration of 1.10 mmol / g, and a urea bond concentration of 0.5 mmol / g.
[0118] (Synthesis Example 4) Pu-4 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube was charged with 90.0 parts of polyester polyol (hydroxyl value: 15.0 mg KOH / g) consisting of propylene glycol, ethylene glycol and succinic acid, 10.0 parts of 1,4 butanediol (hydroxyl value: 1245.0 mg KOH / g) and 35.0 parts of isophorone diisocyanate, and reacted at 100 ° C for 20 hours under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 2.15 mass%, and then 110.4 parts of ethyl acetate were added to this to obtain a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 6.48 parts of isophorone diamine, 0.17 parts of monoethanolamine, 121.5 parts of ethyl acetate and 99.4 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45 ° C for 5 hours to obtain a polyurethane resin solution Pu-4. The resulting polyurethane resin solution Pu-4 had a resin solid concentration of 30.2% by mass, a weight average molecular weight (Mw) of the resin solid content of 83,000, a urethane bond concentration of 1.70 mmol / g, and a urea bond concentration of 0.5 mmol / g.
[0119] (Synthesis Example 5) Pu-5 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube was charged with 98.0 parts of polyester polyol (hydroxyl value: 16.2 mg KOH / g) consisting of propylene glycol, ethylene glycol and succinic acid, 2.0 parts of 1,4 butanediol (hydroxyl value: 1245.0 mg KOH / g) and 14.4 parts of isophorone diisocyanate, and reacted at 100 ° C for 20 hours under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 2.10 mass%, and then 93.6 parts of ethyl acetate was added to the mixture to obtain a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 5.78 parts of isophorone diamine, 0.15 parts of monoethanolamine, 103.5 parts of ethyl acetate and 84.5 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45 ° C for 5 hours to obtain a polyurethane resin solution Pu-5. The resulting polyurethane resin solution Pu-5 had a resin solid concentration of 30.2% by mass, a weight average molecular weight (Mw) of the resin solid content of 83,000, a urethane bond concentration of 0.60 mmol / g, and a urea bond concentration of 0.5 mmol / g.
[0120] (Synthesis Example 6) Pu-6 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube was charged with 95.0 parts of polyester polyol (hydroxyl value: 14.7 mg KOH / g) consisting of propylene glycol, ethylene glycol and succinic acid, 5.0 parts of 1,4 butanediol (hydroxyl value: 1245.0 mg KOH / g) and 18.8 parts of isophorone diisocyanate, and reacted at 100 ° C for 20 hours under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 1.19 mass%, and then 97.2 parts of ethyl acetate were added to the mixture to obtain a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 3.42 parts of isophorone diamine, 0.15 parts of monoethanolamine, 103.3 parts of ethyl acetate and 85.9 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45 ° C for 5 hours to obtain a polyurethane resin solution Pu-6. The resulting polyurethane resin solution Pu-6 had a resin solid concentration of 30.2% by mass, a weight average molecular weight (Mw) of the resin solid content of 83,000, a urethane bond concentration of 1.10 mmol / g, and a urea bond concentration of 0.3 mmol / g.
[0121] (Synthesis Example 7) Pu-7 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube was charged with 95.0 parts of polyester polyol (hydroxyl value: 46.3 mg KOH / g) consisting of propylene glycol, ethylene glycol and succinic acid, 5.0 parts of 1,4 butanediol (hydroxyl value: 1245.0 mg KOH / g) and 49.3 parts of isophorone diisocyanate, and reacted at 100 ° C for 20 hours under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 7.17 mass%, and then 122.2 parts of ethyl acetate were added to the mixture to obtain a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 22.40 parts of isophorone diamine, 0.20 parts of monoethanolamine, 159.2 parts of ethyl acetate and 120.6 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45 ° C for 5 hours to obtain a polyurethane resin solution Pu-7. The resulting polyurethane resin solution Pu-7 had a resin solid concentration of 30.2% by mass, a weight average molecular weight (Mw) of the resin solid content of 83,000, a urethane bond concentration of 1.10 mmol / g, and a urea bond concentration of 1.5 mmol / g.
[0122] (Synthesis Example 8) Pu-8 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube was charged with 95.0 parts of polyester polyol (hydroxyl value: 18.3 mg KOH / g) consisting of propylene glycol, ethylene glycol and dimer acid, 5.0 parts of 1,4 butanediol (hydroxyl value: 1245.0 mg KOH / g) and 22.6 parts of isophorone diisocyanate, and reacted at 100 ° C for 20 hours under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 2.10 mass%, and then 100.3 parts of ethyl acetate was added to the mixture to obtain a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 5.79 parts of isophorone diamine, 0.15 parts of monoethanolamine, 110.2 parts of ethyl acetate and 90.2 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45 ° C for 5 hours to obtain a polyurethane resin solution Pu-8. The resulting polyurethane resin solution Pu-8 had a resin solid concentration of 30.2% by mass, a weight average molecular weight (Mw) of the resin solid content of 83,000, a urethane bond concentration of 1.10 mmol / g, and a urea bond concentration of 0.5 mmol / g.
[0123] (Synthesis Example 9) Pu-9 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube was charged with 95.5 parts of polyester polyol (hydroxyl value: 14.4 mg KOH / g) consisting of propylene glycol, ethylene glycol and succinic acid, 4.5 parts of 1,3 propanediol (hydroxyl value: 1474.6 mg KOH / g) and 22.7 parts of isophorone diisocyanate, and reacted at 100 ° C for 20 hours under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 2.11 mass%, and then 100.4 parts of ethyl acetate was added to the mixture to obtain a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 5.82 parts of isophorone diamine, 0.15 parts of monoethanolamine, 110.4 parts of ethyl acetate and 90.3 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45 ° C for 5 hours to obtain a polyurethane resin solution Pu-9. The resulting polyurethane resin solution Pu-9 had a resin solid concentration of 30.2% by mass, a weight average molecular weight (Mw) of the resin solid content of 83,000, a urethane bond concentration of 1.10 mmol / g, and a urea bond concentration of 0.5 mmol / g.
[0124] (Synthesis Example 10) Pu-10 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube was charged with 96.5 parts of polyester polyol (hydroxyl value: 16.9 mg KOH / g) consisting of propylene glycol, ethylene glycol and succinic acid, 3.5 parts of diethylene glycol (hydroxyl value: 1807.6 mg KOH / g) and 22.6 parts of isophorone diisocyanate, and reacted at 100 ° C for 20 hours under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 2.10 mass%, and then 100.3 parts of ethyl acetate was added to the mixture to obtain a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 5.79 parts of isophorone diamine, 0.15 parts of monoethanolamine, 110.2 parts of ethyl acetate and 90.2 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45 ° C for 5 hours to obtain a polyurethane resin solution Pu-10. The resulting polyurethane resin solution Pu-10 had a resin solid concentration of 30.2% by mass, a weight average molecular weight (Mw) of the resin solid content of 83,000, a urethane bond concentration of 1.10 mmol / g, and a urea bond concentration of 0.5 mmol / g.
[0125] (Synthesis Example 11) Pu-11 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube was charged with 95.0 parts of polyester polyol (hydroxyl value: 18.2 mg KOH / g) consisting of propylene glycol, ethylene glycol and succinic acid, 5.0 parts of 1,4 butanediol (hydroxyl value: 1245.0 mg KOH / g) and 22.6 parts of isophorone diisocyanate, and reacted at 100 ° C for 20 hours under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 2.11 mass%, and then 100.3 parts of ethyl acetate was added to the mixture to obtain a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 5.81 parts of isophorone diamine, 0.15 parts of monoethanolamine, 110.2 parts of ethyl acetate and 90.2 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45 ° C for 5 hours to obtain a polyurethane resin solution Pu-11. The resulting polyurethane resin solution Pu-11 had a resin solid concentration of 30.2% by mass, a weight average molecular weight (Mw) of the resin solid content of 83,000, a urethane bond concentration of 1.10 mmol / g, and a urea bond concentration of 0.5 mmol / g.
[0126] (Synthesis comparative example 1) Pu-12 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube was charged with 99.0 parts of polyester polyol consisting of ethylene glycol and succinic acid (hydroxyl value: 67.8 mg KOH / g), 1.0 parts of 1,4 butanediol (hydroxyl value: 1245.0 mg KOH / g) and 22.6 parts of isophorone diisocyanate, and reacted at 100 ° C for 20 hours under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 2.11 mass%, and then 100.3 parts of ethyl acetate was added to this to make a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 5.81 parts of isophorone diamine, 0.15 parts of monoethanolamine, 110.2 parts of ethyl acetate and 90.2 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45 ° C for 5 hours to obtain a polyurethane resin solution Pu-12. The resulting polyurethane resin solution Pu-12 had a resin solid concentration of 30.2% by mass, a weight average molecular weight (Mw) of the resin solid content of 83,000, a urethane bond concentration of 1.10 mmol / g, and a urea bond concentration of 0.5 mmol / g.
[0127] (Synthesis comparative example 2) Pu-13 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube was charged with 99.0 parts of polyester polyol (hydroxyl value: 36.1 mg KOH / g) consisting of propylene glycol and succinic acid, 1.0 parts of 1,4 butanediol (hydroxyl value: 1245.0 mg KOH / g) and 16.0 parts of isophorone diisocyanate, and reacted at 100 ° C for 20 hours under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 2.10 mass%, and then 94.9 parts of ethyl acetate was added to this to make a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 5.49 parts of isophorone diamine, 0.15 parts of monoethanolamine, 104.3 parts of ethyl acetate and 85.4 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45 ° C for 5 hours to obtain a polyurethane resin solution Pu-13. The obtained polyurethane resin solution Pu-13 had a resin solid concentration of 30.2 mass%, a weight average molecular weight (Mw) of the resin solid content of 83,000, a urethane bond concentration of 0.70 mmol / g, and a urea bond concentration of 0.5 mmol / g.
[0128] (Synthesis comparative example 3) Pu-14 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube was charged with 89.0 parts of a polyester polyol consisting of propylene glycol and succinic acid (hydroxyl value: 27.2 mg KOH / g), 10 parts of polyethylene glycol (hydroxyl value: 112.2 mg KOH / g), 1.0 part of 1,4-butanediol (hydroxyl value: 1245.0 mg KOH / g), and 15.9 parts of isophorone diisocyanate, and reacted at 100°C for 20 hours under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 2.09 mass%, to which was added 94.8 parts of ethyl acetate to obtain a homogeneous solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 5.48 parts of isophoronediamine, 0.15 parts of monoethanolamine, 104.2 parts of ethyl acetate, and 85.3 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45°C for 5 hours to obtain polyurethane resin solution Pu-14. The obtained polyurethane resin solution Pu-14 had a resin solid content concentration of 30.2 mass%, a weight average molecular weight (Mw) of the resin solid content of 83,000, and a urethane bond concentration of 0.70 mmol / g. The urea bond concentration was 0.5 mmol / g.
[0129] (Synthesis comparative example 4) Pu-15 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube was charged with 100.0 parts of polyester polyol (hydroxyl value: 33.4 mg KOH / g) consisting of propylene glycol, ethylene glycol and succinic acid and 12.9 parts of isophorone diisocyanate, and reacted for 20 hours at 100 ° C under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 2.09 mass%, and then 92.3 parts of ethyl acetate was added to the mixture to obtain a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 5.34 parts of isophorone diamine, 0.14 parts of monoethanolamine, 101.5 parts of ethyl acetate and 83.1 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45 ° C for 5 hours to obtain a polyurethane resin solution Pu-15. The resulting polyurethane resin solution Pu-15 had a resin solid concentration of 30.2% by mass, a weight average molecular weight (Mw) of the resin solid content of 83,000, a urethane bond concentration of 0.50 mmol / g, and a urea bond concentration of 0.5 mmol / g.
[0130] (Synthesis Comparative Example 5) Pu-16 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube was charged with 99.0 parts of polyester polyol (hydroxyl value: 35.6 mg KOH / g) consisting of propylene glycol, neopentyl glycol and succinic acid, 1.0 parts of 1,4 butanediol (hydroxyl value: 1245.0 mg KOH / g) and 15.8 parts of isophorone diisocyanate, and reacted at 100 ° C for 20 hours under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 2.09 mass%, and then 94.8 parts of ethyl acetate was added to this to make a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 5.47 parts of isophorone diamine, 0.14 parts of monoethanolamine, 104.2 parts of ethyl acetate and 85.3 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45 ° C for 5 hours to obtain a polyurethane resin solution Pu-16. The resulting polyurethane resin solution Pu-16 had a resin solid concentration of 30.2% by mass, a weight average molecular weight (Mw) of the resin solid content of 83,000, a urethane bond concentration of 0.70 mmol / g, and a urea bond concentration of 0.5 mmol / g.
[0131] (Synthesis Example 12) Pu-17 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube was charged with 95.0 parts of polyester polyol (hydroxyl value: 20.0 mg KOH / g) consisting of propylene glycol, ethylene glycol and adipic acid, 5.0 parts of 1,4 butanediol (hydroxyl value: 1245.0 mg KOH / g) and 22.9 parts of isophorone diisocyanate, and reacted at 100 ° C for 20 hours under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 2.09 mass%, and then 100.5 parts of ethyl acetate was added to the mixture to obtain a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 5.79 parts of isophorone diamine, 0.15 parts of monoethanolamine, 110.4 parts of ethyl acetate and 90.4 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45 ° C for 5 hours to obtain a polyurethane resin solution Pu-17. The resulting polyurethane resin solution Pu-17 had a resin solid concentration of 30.2% by mass, a weight average molecular weight (Mw) of the resin solid content of 83,000, a urethane bond concentration of 1.10 mmol / g, and a urea bond concentration of 0.5 mmol / g.
[0132] (Synthesis Example 13) Pu-B1 In a four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube, 90 parts of polyester polyol (hydroxyl value: 25 mg KOH / g) made from neopentyl glycol and sebacic acid, 10 parts of polyethylene glycol (hydroxyl value: 55 mg KOH / g) and 11.7 parts of isophorone diisocyanate were charged and reacted for 10 hours at 90 ° C under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 2.10 mass%, and then 91.4 parts of ethyl acetate were added to the mixture to obtain a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 7.09 parts of isophorone diamine, 0.92 parts of di-n-butylamine, 100.5 parts of ethyl acetate and 82.3 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45 ° C for 5 hours to obtain a polyurethane resin solution Pu-B1. The resulting polyurethane resin solution Pu-B1 had a resin solid concentration of 30.0% by mass, a weight average molecular weight (Mw) of the resin solid content of 60,000, a urethane bond concentration of 0.4 mmol / g, and a urea bond concentration of 0.5 mmol / g.
[0133] (Synthesis Example 14) Pu-B2 In a four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube, 90 parts of polyester polyol (hydroxyl value: 25 mg KOH / g) made from neopentyl glycol and succinic acid, 10 parts of polyethylene glycol (hydroxyl value: 55 mg KOH / g) and 11.7 parts of isophorone diisocyanate were charged and reacted for 10 hours at 90 ° C under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 2.10 mass%, and then 91.4 parts of ethyl acetate were added to the mixture to obtain a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 7.09 parts of isophorone diamine, 0.92 parts of di-n-butylamine, 100.5 parts of ethyl acetate and 82.3 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45 ° C for 5 hours to obtain a polyurethane resin solution Pu-B2. The resulting polyurethane resin solution Pu-B2 had a resin solid concentration of 30.0% by mass, a weight average molecular weight (Mw) of the resin solid content of 60,000, a urethane bond concentration of 0.4 mmol / g, and a urea bond concentration of 0.5 mmol / g.
[0134] (Synthesis Example 15) Pu-B3 In a four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube, 90 parts of polyester polyol (hydroxyl value: 25 mg KOH / g) made from neopentyl glycol and adipic acid, 10 parts of polyethylene glycol (hydroxyl value: 55 mg KOH / g) and 11.7 parts of isophorone diisocyanate were charged and reacted for 10 hours at 90 ° C under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 2.10 mass%, and then 91.4 parts of ethyl acetate were added to the mixture to obtain a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 7.09 parts of isophorone diamine, 0.92 parts of di-n-butylamine, 100.5 parts of ethyl acetate and 82.3 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45 ° C for 5 hours to obtain a polyurethane resin solution Pu-B3. The resulting polyurethane resin solution Pu-B3 had a resin solid concentration of 30.0% by mass, a weight average molecular weight (Mw) of the resin solid content of 60,000, a urethane bond concentration of 0.4 mmol / g, and a urea bond concentration of 0.5 mmol / g.
[0135] (Synthesis Example 16) Pu-B4 In a four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube, 100 parts of polyester polyol (hydroxyl value: 26.9 mgKOH / g) made from neopentyl glycol and sebacic acid as raw materials and 11.5 parts of isophorone diisocyanate were charged, and reacted at 90°C for 10 hours under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 2.09% by mass, and then 91.2 parts of ethyl acetate were added to the mixture to obtain a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 5.19 parts of isophorone diamine, 0.30 parts of di-n-butylamine, 100.3 parts of ethyl acetate and 82.0 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45°C for 5 hours to obtain a polyurethane resin solution Pu-B4. The resulting polyurethane resin solution Pu-B4 had a resin solid concentration of 29.9% by mass, a weight average molecular weight of the resin solid content of 54,000, a urethane bond concentration of 0.4 mmol / g, and a urea bond concentration of 0.5 mmol / g.
[0136] (Synthesis Example 17) Pu-B5 In a four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet tube, 100 parts of polyester polyol (hydroxyl value: 26.9 mgKOH / g) made from neopentyl glycol and succinic acid and 11.5 parts of isophorone diisocyanate were charged, and reacted for 10 hours at 90°C under a nitrogen stream to produce a urethane prepolymer with an isocyanate group content of 2.09% by mass, and then 91.2 parts of ethyl acetate were added to the mixture to obtain a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture consisting of 5.19 parts of isophorone diamine, 0.30 parts of di-n-butylamine, 100.3 parts of ethyl acetate and 82.0 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45°C for 5 hours to obtain a polyurethane resin solution Pu-B5. The resulting polyurethane resin solution Pu-B5 had a resin solid concentration of 29.9% by mass, a weight average molecular weight of the resin solid content of 54,000, a urethane bond concentration of 0.4 mmol / g, and a urea bond concentration of 0.5 mmol / g.
[0137] (Preparation of vinyl chloride / vinyl acetate copolymer resin solution) A hydroxyl group-containing vinyl chloride-vinyl acetate copolymer resin (resin monomer composition by weight: vinyl chloride / vinyl acetate / vinyl alcohol=92 / 3 / 5, hydroxyl value (mgKOH)=64) used in combination with polyurethane resin was made into a 15% solution in ethyl acetate, and this was named the vinyl chloride-vinyl acetate resin solution (Ev).
[0138] [Example 1] A mixture of 30 parts of the obtained polyurethane resin solution Pu-1, 10 parts of a hydroxyl group-containing vinyl chloride / vinyl acetate copolymer resin solution Ev (15% solution), 35 parts of a white pigment (alumina and silica-surface-treated titanium oxide pigment R-780, manufactured by Ishihara Sangyo Kaisha, Ltd.), and 30 parts of ethyl acetate was kneaded to prepare a white printing ink.
[0139] [Examples 2 to 21, Comparative Examples 1 to 5] In the same manner as in Example 1, the indigo printing inks of Examples 2 to 21 and Comparative Examples 1 to 5 were prepared with the formulations shown in Tables 1 to 5.
[0140] (Low temperature crystallization) 100 ml of the prepared printing ink was weighed out and placed in a 125 ml airtight container, which was then sealed and left to stand in a refrigerator at 0°C for 3 days. The container was then removed from the refrigerator and the occurrence of solid matter due to aggregation was visually evaluated.
[0141] (Evaluation Criteria) ○: No solids were found ×: Solid matter was observed The viscosity of the obtained printing ink was adjusted to 16 seconds (25°C) using ethyl acetate in a Zahn cup #3 (manufactured by Rigo Co., Ltd.), and printed on the vapor-deposited surfaces of a biaxially oriented polypropylene film (hereinafter referred to as OPP), a nylon film (ON-RT (15 μm) manufactured by Unitika Ltd., hereinafter referred to as NY), and an alumina-deposited transparent PET film (IB-PET-PUB (thickness: 12 μm) manufactured by Dai Nippon Printing Co., Ltd., hereinafter referred to as PET / AL), each of which had been corona-treated on one side, using a gravure proofing machine equipped with a gravure plate with a plate depth of 35 μm, and dried at 40 to 50°C to obtain prints.
[0142] The obtained printed matter was measured and evaluated for extrusion laminate strength and dry laminate strength, and the results are shown in Table 1. The evaluation was performed by the following test methods.
[0143] (Extrusion Laminate Strength) A polyethyleneimine-based anchor coating agent is applied to the OPP printed material at 0.1 g / m 2 After coating, molten polyethylene was laminated to a thickness of 40 μm using an extrusion laminator. After obtaining a laminated product, the laminate film was cut to a width of 15 mm and subjected to a 90° peel test at a pulling speed of 50 mm / min.
[0144] (Dry laminate strength) The printed surface of the PET / AL print was coated with a urethane-based dry lamination adhesive DIC Dry LX-703VL / KR-90 (DIC) using a dry laminator (DIC Engineering), and a non-oriented polypropylene film (hereinafter, R-CPP: ZK-207 70 μm, Toray Synthetic Films Co., Ltd.) was laminated onto the adhesive-coated surface. The laminate was then aged at 40° C. for 5 days to obtain a laminate.
[0145] Similarly, for the NY printed matter, the printed surface was coated with a urethane-based dry laminating adhesive DIC Dry LX-703VL / KR-90 (DIC) using a dry laminating machine (DIC Engineering), and a non-oriented low-density polyethylene film (hereinafter, LLDPE: TUX-HC 60μm, Mitsui Chemicals Tohcello Co., Ltd.) was laminated onto the adhesive-coated surface. The laminate was then aged at 40°C for 5 days to obtain a laminate.
[0146] The obtained laminate was cut into a width of 15 mm and subjected to a 90° peel test at a pulling speed of 300 mm / min.
[0147] (Printability (plate fog)) The viscosity of the obtained liquid printing ink was adjusted to 16 seconds (25°C) using a Zahn cup #3 (manufactured by Rigo Co., Ltd.) with a mixed organic solvent of ethyl acetate / isopropyl alcohol = 80 / 20, and printing was performed on the treated side of a PET film that had been corona discharge treated on one side using an MD type gravure printing machine (manufactured by Fuji Machine Co., Ltd.) equipped with a laser gravure plate with a plate depth of 30 μm. The degree of dirt (plate fogging) in the non-printed highlight areas when printing with a gravure plate circumference of 600 mmφ at a printing speed of 200 m / min was visually evaluated.
[0148] (Evaluation Criteria) ◎: No stains at all on non-printed areas ○: There is a small amount of dirt on the non-printed areas. △: Conspicuous staining of non-printed areas
[0149] [Table 1]
[0150] [Table 2]
[0151] [Table 3]
[0152] [Table 4]
[0153] [Table 5]
[0154] From the above results, the liquid ink composition of the present invention shown in the examples did not crystallize at low temperatures, and excellent results were obtained in both extrusion laminate strength and dry laminate strength. Furthermore, the liquid ink composition of the present invention also provided excellent laminate strength when a vapor-deposited film was used.
Claims
1. A liquid ink composition comprising a binder resin containing a polyurethane resin (A) and an organic solvent, The polyurethane resin (A) uses a polyol and a polyisocyanate compound as reaction raw materials, and contains at least a polyester polyol (a1) and a diol (a2) having 1 to 20 carbon atoms as the polyol, The polyester polyol (a1) is produced by using two or more diols as reaction raw materials, and contains ethylene glycol as an essential diol, The diol (a2) having 1 to 20 carbon atoms is selected from 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, and diethylene glycol; The weight average molecular weight of the polyurethane resin (A) is within the range of 15,000 to 150,000. A liquid ink composition for flexible packaging laminate, comprising:
2. The polyurethane resin (A) does not contain polyethylene glycol as the polyol. The liquid ink composition according to claim 1 .
3. The polyurethane resin (A) has a urethane bond concentration of 0.6 mmol / g or more. The liquid ink composition according to claim 1 or 2.
4. The polyurethane resin (A) has a urea bond, and the concentration of the urea bond in the polyurethane resin (A) is 1.5 mmol / g or less. The liquid ink composition according to claim 1 or 2.
5. The number average molecular weight of the polyester polyol (a1) is 1,500 to 8,000. The liquid ink composition according to claim 1 or 2.
6. 3. The liquid ink composition according to claim 1, wherein a mass ratio of the polyester polyol (a1) to the diol (a2) is polyester polyol (a1):(a2)=99.5:0.5 to 70:
30.
7. 3. The liquid ink composition according to claim 1, wherein in the polyurethane resin (A), the proportion of solid components derived from biomass raw materials in the polyester polyol that is a reaction raw material is 30 mass% or more.
8. 3. The liquid ink composition according to claim 1 or 2, further comprising, as the binder resin, at least one resin selected from the group consisting of a polyurethane resin (B) other than the polyurethane resin (A), a vinyl chloride-vinyl acetate copolymer resin, a cellulose-based resin, a polyester resin, an acrylic resin, a polyamide resin, and a rosin-based resin.
9. 9. The liquid ink composition according to claim 8, wherein the urethane bond concentration of the polyurethane resin (B) is lower than the urethane bond concentration of the polyurethane resin (A).
10. The liquid ink composition according to claim 8, wherein the polyurethane resin (A) and / or the polyurethane resin (B) contains a component derived from a biomass raw material.
11. The mass ratio of the polyurethane resin (A) to the polyurethane resin (B) in terms of solid components is polyurethane resin (A):polyurethane resin (B)=40:60 to 95:
5. The liquid ink composition according to claim 8.
12. Contains 0 to 10% by mass of water. The liquid ink composition according to claim 1 or 2.
13. A printed matter obtained by printing the liquid ink composition according to claim 1 or 2 on a substrate.
14. A laminate or package comprising the printed matter according to claim 13.
Citation Information
Patent Citations
Method for controlling copying machine
JP1987099765A
Gravure printing ink composition for surface printing
JP2018058979A
Solvent type gravure ink for laminate, printed matter, and laminate
JP2018076461A
Liquid ink composition
JP2019006910A
Liquid ink composition
JP2019123810A